Effect of Vote Buying on Election Credibility During the 2023 Gubernatorial Elections in Taraba State - Solomon Tsokwa; Ibrahim Danjuma Tigye (Darul Yasin Al Sys, 2025)
This study investigates the prevalence, methods, and impacts of vote buying during the 2023 gubernatorial election in Taraba State, Nigeria. Using a descriptive survey research design, the study aimed to examine respondents' attitudes, perceptions, and opinions regarding vote buying. Data were collected using a structured questionnaire from a sample of 390 respondents, selected through a multi-stage sampling technique across three senatorial zones in Taraba State. The sample included voters who had participated in the election, with purposive sampling used to ensure representation. The findings reveal that vote buying was a widespread issue, with financial and material incentives, such as cash and gifts, being the primary methods employed by politicians. The study identified several factors contributing to the prevalence of vote buying, including economic hardship, lack of political education, weak enforcement of electoral laws, and low trust in political institutions. Furthermore, the practice of vote buying significantly influenced voters' decisions, with many indicating that financial inducements swayed their voting choices. The study concludes that vote buying undermines the integrity of the electoral process and has serious implications for democratic governance in Nigeria. The researcher recommends strengthening electoral laws, enhancing voter education, addressing economic inequality, and promoting transparency in campaign financing to reduce the prevalence of vote buying in future elections.